The Effect of Intravenous Dexamethasone on Postoperative Nausea and Vomiting After Cesarean Delivery With Intrathecal Morphine: A Randomized-controlled Trial. Issue 2 (24th June 2021) - Selzer, A.; Pryor, K.O.; Tangel, V.; O'Connell, K.; Kjaer, K.
Abstract : ( Can J Anesth . 2020;67:817–826) For women having a cesarean delivery, the estimated incidence of postoperative nausea and vomiting (PONV) ranges from 30% to 80%. Compared with spinal anesthesia without intrathecal opioid, the administration of intrathecal morphine has been associated with an increase in PONV, by up to 5-fold. According to one meta-analysis, the administration of intravenous (IV) dexamethasone showed a significant reduction in PONV in patients receiving epidural morphine – but not among those receiving intrathecal morphine. In the meta-analysis, 6 randomized-controlled trials (RCTs) studied the use of IV dexamethasone prior to epidural morphine and 2 RCTs studied its use prior to the end of surgery but not before intrathecal morphine administration. Whether the timing of IV dexamethasone is important for prophylaxis of PONV remains unclear. The aim of this study was to determine whether intravenous dexamethasone reduces the incidence of PONV when administered prior to intrathecal morphine during spinal anesthesia.